PEMBUATAN PRODUK INOVASI KERIPIK SAWO DI DESA MLANDINGAN WETAN KABUPATEN SITUBONDO - Wahyuningsi, Nurin Kartika; Husna, Zahra Nafilatul; Idris, Albani; Romla, Siti; Jannah, Raudatul (STKIP PGRI SITUBONDO, 2025)
Mlandingan Wetan Village has various interesting potentials starting from the abundant harvest in the village and innovations have not been carried out such as the presence of sapodilla fruit falling in residents' yards. The gap between the large potential of sapodilla fruit and the limited products is an important reason for implementing community service in Mlandingan Wetan Village. In order to utilize the knowledge gained regarding village product innovation that can increase the value of a product by utilizing the potential of natural resources in a village to be able to improve the economy of residents in Mlandingan Wetan by innovating the processing of sapodilla fruit into sapodilla fruit chips. PBPMD participants finally carried out the innovation of